Development of selective, fluorescent cannabinoid type 2 receptor ligands based on a 1, 8-naphthyridin-2-(1H)-one-3-carboxamide scaffold. Issue 12 (1st November 2018) - Cooper, Anna G.; Oyagawa, Caitlin R. M.; Manning, Jamie J.; Singh, Sameek; Hook, Sarah; Grimsey, Natasha L.; Glass, Michelle; Tyndall, Joel D. A.; Vernall, Andrea J.
Abstract : High affinity, cannabinoid type 2 receptor selective ligand. Abstract : Cannabinoid type 2 (CB2 ) receptor has been implicated in several diseases and conditions, however no CB2 receptor selective drugs have made it to market. The aim of this study was to develop fluorescent ligands as CB2 receptor tools, to enable an increased understanding of CB2 receptor expression and signalling and thereby accelerate drug discovery. Fluorescent ligands have been successfully developed for other receptors, however none with adequate subtype selectivity or imaging properties have been reported for CB2 receptor. A series of 1, 8-naphthyridin-2-(1 H )-one-3-carboxamides with linkers and fluorophores appended in the N1 and C3-positions were developed. Molecular modelling indicated the C3 cis -cyclohexanol-linked compounds directed the linker out of the CB2 receptor between transmembrane helices 1 and 7. Herein we report fluorescent ligand32 (hCB2 p K i = 6.33 ± 0.02) as one of the highest affinity, selective CB2 receptor fluorescent ligands reported. Despite32 displaying poor specific labelling of CB2 receptor, the naphthyridine scaffold with this linker remains highly promising for future development of CB2 receptor tools.